2008
DOI: 10.1158/1078-0432.ccr-08-0523
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Gene Expression in Early-Stage Ovarian Cancer

Abstract: Purpose: Gene expression profile was analyzed in 68 stage I and 15 borderline ovarian cancers to determine if different clinical features of stage I ovarian cancer such as histotype, grade, and survival are related to differential gene expression. Experimental Design:Tumors were obtained directly at surgery and immediately frozen in liquid nitrogen until analysis. Glass arrays containing 16,000 genes were used in a dual-color assay labeling protocol. Results: Unsupervised analysis identified eight major patien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 48 publications
0
36
0
1
Order By: Relevance
“…We previously demonstrated that increased CD47 mRNA expression levels were correlated with poor clinical outcomes in patients with acute myeloid leukemia and non-Hodgkin's lymphoma (16,17). To determine if CD47 mRNA expression levels were also a prognostic factor in human solid tumors, we analyzed gene-expression data from several previously described cohorts of patients with ovarian cancers, gliomas, and glioblastomas (Table S1) (18)(19)(20)(21)(22)(23)(24)(25). In a univariate analysis, stratification of patients into "CD47 high" and "CD47 low" groups based on an optimum threshold revealed that high CD47 mRNA expression levels were associated with a decreased probability of progression-free ( Fig.…”
Section: Cd47 Ismentioning
confidence: 99%
“…We previously demonstrated that increased CD47 mRNA expression levels were correlated with poor clinical outcomes in patients with acute myeloid leukemia and non-Hodgkin's lymphoma (16,17). To determine if CD47 mRNA expression levels were also a prognostic factor in human solid tumors, we analyzed gene-expression data from several previously described cohorts of patients with ovarian cancers, gliomas, and glioblastomas (Table S1) (18)(19)(20)(21)(22)(23)(24)(25). In a univariate analysis, stratification of patients into "CD47 high" and "CD47 low" groups based on an optimum threshold revealed that high CD47 mRNA expression levels were associated with a decreased probability of progression-free ( Fig.…”
Section: Cd47 Ismentioning
confidence: 99%
“…Data previously published by our group deciphered a molecular circuit in stage I EOC, revealing miR-200c as an independent prognostic factor (6,7). Focusing our study on the miRNA profiles, we studied the differences among stage I EOC histologic types looking for specific markers and regulatory circuits.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested by several studies that different histological types of ovarian cancers represent distinct disease entities [4][5][6]; in fact, it appears that endometrioid ovarian cancer arises probably from the metaplastic Mullerian epithelium rather than the ovarian surface celomatic sheet, which is more likely in the case of serous carcinoma. This reflects the fact that gene expression profiles are different in the two histological types regardless of the stage and grade of the disease [7].…”
Section: Introductionmentioning
confidence: 99%